KELAYAKAN POSTER LIPAT SUB MATERI PEMANFAATAN KEANEKARAGAMAN HAYATI DI KELAS X SMA - Irwanti, Muthia; Syamswisna, Syamswisna; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis research aimed to determine the feasibility of folded poster on sub-material utilization of biodiversity in class X Senior High School. The folded poster was based on the syllabus analysis and the results of the ethnobotany study of women's self-care in the Palace of the Kadriyah Sultanate of Pontianak. The type of research used is descriptive qualitative research. The systematics of this research consists of three stages, namely the creation of folded poster media, folded poster media validation, and data analysis. Folded poster media that have been printed are validated by two biology lecturers and three biology high school teachers to find out their feasibility as a learning media in the sub-material utilization of biodiversity in class X Senior High School. Before the folded poster media was validated, media instrument validation was carried out first. The assessment results of the five validators are then analyzed used CVR (Content Validity Ratio) and CVI (Content Validity Index) analysis. Although the CVR value of criterion number 15 is 0.6 and the CVR value of criteria number 1 to 14 is 0.99 respectively. The CVI value on the 15 criteria is declared valid by obtaining a value of 0.97 because it is in the range of 0-1.Keywords:Â Feasibility, Palace of the Kadriyah Sultanate of Pontianak, Utilization of Biodiversity, and Folded Poster